One stone two birds: a sinter-resistant TiO2 nanofiber-based unbroken mat enables PM capture and in situ elimination. Issue 48 (6th December 2021) - Xu, Wanlin; Fu, Wanlin; Meng, Xiangyu; Tang, Mingyu; Huang, Chaobo; Sun, Yueming; Dai, Yunqian
Abstract : Fragile TiO2 nanofibers was functionalized with good structural integrity, flexibility, and foldability, by depressing the sintering of nanocrystallites, enabling PM capture and in situ elimination via a "one-stone-two-birds" approach. Abstract : Airborne particulate matter (PM) primarily resulting from fossil fuel burning is an increasingly global issue. In this work, an intrinsically fragile TiO2 nanofibrous mat was facilely engineered with good structural integrity, flexibility, foldability, and high-temperature resistance ( 1300 °C), by suppressing the sintering ( i.e., growth) of nanocrystallites in each single nanofiber. Such functionalization enables self-regenerative air filtration for PM capture and in situ catalytic elimination in a "one-stone-two-birds" approach. Finite element analysis simulation revealed the retained nanopores in each anti-sintering nanofiber could facilitate the air flow during filtration. Without any chemical or physical modification, this self-standing and lightweight (7.1 g m −2 ) fibrous mat showed 96.05% filtration efficiency for 3–5 μm NaCl particles, with a low pressure drop of only 18 Pa and high quality factor of 0.179 Pa −1 under an airflow velocity of 32 L min −1 . By utilizing its photocatalytic attribute, the nanofibrous mat in situ eliminated the captured particles from incense burning under one Sun irradiation in 4 h, and thereby spontaneously regenerated in an easy manner. The straightforward grafting of Au nanoparticles onto nanofibers could enable a quick degradation toward cigarette smoke, mainly due to the photothermally elevated local temperature by Au around the reactive sites. The plasmonic fibrous mat kept a high and stable filtration efficiency of PM0.3, PM2.5, and PM10 over 98.62%, 99.76%, and 99.99% during an outdoor long-term filtration test for 12 h under sunlight irradiation (Nanjing, China, September, 26 th, 2020, 7:30 to 19:30). This work provides a solution for solving the airborne pollution from its source, prolonging the lifetime of the filter, and avoiding the risk of producing secondary pollution.